Design, synthesis and biological evaluation of novel orthosteric-allosteric ligands of the cannabinoid receptor type 2 (CB2R) - Ferrisi, Rebecca; Gado, Francesca; Polini, Beatrice; Ricardi, Caterina; Mohamed, Kawthar A.; Stevenson, Lesley A.; Ortore, Gabriella; Rapposelli, Simona; Saccomanni, Giuseppe; Pertwee, Roger G.; Laprairie, Robert B.; Manera, Clementina; et al. (Frontiers in Chemistry, 2022)
It is well known that G protein–coupled receptors (GPCRs) assume multiple active states. Orthosteric ligands and/or allosteric modulators can preferentially stabilize specific conformations, giving rise to pathway-biased signalling. One of the most promising strategies to expand the repertoire of signaling-selective GPCR activators consists of dualsteric agents, which are hybrid compounds consisting of orthosteric and allosteric pharmacophoric units. This approach proved to be very promising showing several advantages over monovalent targeting strategies, including an increased affinity or selectivity, a bias in signalling pathway activation, reduced off-target activity and therapeutic resistance. Our study focused on cannabinoid receptor 2 (CB2R), considered a clinically promising target for the control of brain damage in neurodegenerative disorders. Indeed, CB2R was found highly expressed in microglial cells, astrocytes, and even in some neuron subpopulations. Here, we describe the design, synthesis, and biological evaluation of two new classes of potential dualsteric (bitopic) CB2R ligands. The new compounds were obtained by connecting, through different linkers, the pharmacophoric portion of the CB2R positive allosteric modulator (PAM), EC21a, with that of the CB2R selective orthosteric agonists LV62, both developed in our laboratories. A preliminary screening enabled us to identify compound JR64a as the most promising of the series. Indeed, functional examination highlighted a significant signaling ‘bias’ in favor of G protein activation over βarrestin2 recruitment, combined to high affinity for the CB2R and the ability to efficiently prevent inflammation in human microglial cells (HMC3) exposed to LPS/TNF stimulation, thus demonstrating great promise for the treatment of neurodegenerative diseases.